PEMAHAMAN KEAGAMAAN DAN SIKAP MODERASI: BAGAIMANA HUBUNGANNYA DENGAN PESERTA DIDIK? - Susanti, Agus (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
This study aims to determine the relationship between religious understanding and religious moderation attitudes among students of SMP Negeri 11 Bandar Lampung. The main problem underlying this study is the continued presence of students with narrow and less moderate religious understanding, which has the potential to lead to intolerance in the school environment. This study measures the extent to which the level of religious understanding influences students' religious moderation attitudes. . The method used is a quantitative approach with a correlational design, using the Pearson Product Moment correlation analysis technique to determine the strength and direction of the relationship between the two variables. The study population was all students of SMP Negeri 11 Bandar Lampung, with a sample size of 117 students selected through a purposive sampling technique according to predetermined criteria. Data were obtained through a questionnaire designed based on indicators of religious understanding and religious moderation. The research instrument was validated through internal reliability analysis using the Corrected Item-Total Correlation indicator and reliability testing using the Cronbach's Alpha method to ensure item consistency. Furthermore, prerequisite analysis tests, including normality and linearity tests, were conducted before hypothesis testing. The results showed a positive and significant relationship between religious understanding and religious moderation. The Pearson correlation test yielded an r value of 0.815 with a significance level of p < 0.01, indicating that the higher a student's religious understanding, the higher their religious moderation. Thus, the research hypothesis was accepted, proving that a sound religious understanding plays a significant role in shaping religious moderation among students at SMP Negeri 11 Bandar Lampung. ABSTRAK Penelitian ini bertujuan untuk mengetahui hubungan antara pemahaman keagamaan dengan sikap moderasi beragama pada siswa SMP Negeri 11 Bandar Lampung. Permasalahan utama yang melatarbelakangi penelitian ini adalah masih ditemukannya siswa dengan pemahaman keagamaan yang sempit dan kurang moderat sehingga berpotensi menimbulkan sikap intoleransi di lingkungan sekolah. Penelitian ini mengukur sejauh mana tingkat pemahaman keagamaan berpengaruh terhadap sikap moderasi beragama siswa. Metode yang digunakan adalah pendekatan kuantitatif dengan desain korelasional, menggunakan teknik analisis korelasi Product Moment Pearson untuk mengetahui kekuatan dan arah hubungan kedua variabel. Populasi penelitian adalah seluruh siswa SMP Negeri 11 Bandar Lampung, dengan jumlah sampel 117 siswa yang dipilih melalui teknik purposive sampling sesuai kriteria yang telah ditetapkan. Data diperoleh melalui kuesioner yang disusun berdasarkan indikator pemahaman keagamaan dan sikap moderasi beragama. Instrumen penelitian diuji melalui uji validitas menggunakan analisis reliabilitas internal dengan indikator Corrected Item-Total Correlation dan uji reliabilitas menggunakan metode Cronbach’s Alpha untuk memastikan konsistensi item pertanyaan. Selanjutnya dilakukan uji prasyarat analisis yang meliputi uji normalitas dan uji linearitas sebelum pengujian hipotesis. Hasil penelitian menunjukkan bahwa terdapat hubungan positif dan signifikan antara pemahaman keagamaan dan sikap moderasi beragama. Uji korelasi Pearson menghasilkan nilai r = 0,815 dengan signifikansi p < 0,01, yang berarti semakin tinggi pemahaman keagamaan siswa maka semakin tinggi pula sikap moderasi beragamanya. Dengan demikian, hipotesis penelitian diterima dan membuktikan bahwa pemahaman keagamaan yang baik berperan penting dalam membentuk sikap moderasi beragama di kalangan siswa SMP Negeri 11 Bandar Lampung..